PENYULUHAN “ISI PIRINGKU” UNTUK PENINGKATAN IMUNITAS ANAK DESA KARANG BUNGA - Miranti, Rizka Mulya; Lestari, Yulianita Pratiwi Indah; Mulyani, Tuty; Fajeriyati, Nurul; Rahmawati, Rahmawati; Mustharah, Mustika; Salsabilla, Syifa Aulia; Sazidan, Akhbar Arya Jouraist; Sari, Cindy Fransiska; Amalia, Rizka; Safitri, Salsabila Nurlaila (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Many children only want to eat the foods they like, such as sweet, salty, or high-carbohydrate foods, while vegetables and fruits are often ignored. This unbalanced diet can lead to children lacking essential nutrients needed to maintain immunity and optimal growth. "Isi Piringku" is a government program aimed at raising public awareness about balanced nutrition and healthy eating patterns. The activity aims to improve students' understanding in Desa Karang Bunga regarding the importance of a balanced diet through the "Isi Piringku" education program. This activity, conducted on June 27, 2024, utilized presentation media, demonstrations, and evaluations to measure the increase in knowledge and satisfaction. During the activity, students received explanations about the introduction of "Isi Piringku" in arranging a balanced diet, including carbohydrates, proteins, fats, fruits, and vegetables, and demonstrations were conducted. The results of the activity showed an increase in students' understanding of the importance of balanced nutrition, and satisfaction evaluations indicated positive responses from Desa Karang Bunga.